Tackling responsible lending obligation in Malaysia: a diverse approach - Hassan, Rusni; Kassim, Salina; Abu Bakar, Elistina; Ilias, Ibtisam @ Ilyana; Hingun, Mohsin (Science and Engineering Research Support Society (SERSC), 2019)
This paper examines responsible lending obligation among various credit providers under the present legal and institutional framework in Malaysia. The scope of consumer credit industry includes banking, hire-purchase, moneylending and pawnbroking. The study finds an inconsistent approach in dealing with responsible lending whereby only banking institutions regulated by the Central Bank of Malaysia are subject to this obligation while non-bank institutions are not. Several recommendations for future improvements are proposed by referring to the practice of several other jurisdictions. The suggestions will help the policymakers to seriously consider imposing this obligation on all credit providers. Eventually, the protection against the irresponsible lending practice is accorded to a wide range of financial consumers in consumer credit industry in Malaysia.